Chemical composition and biological activities of the leaves essential oil of Alphonsea monogyna collected in Hue city - Hoang, Xuan Huyen Trang; Le, Thi Truc; Dinh, Dien; Doan, Quoc Tuan (Tạp chí Y Dược Huế, 2026)
Background: Alphonsea monogyna (Roxb.) Hook.f. & Thomson belongs to the genus Alphonsea, distributed in Southeast Asian countries. Information on the chemical composition and biological properties of A. monogyna remains limited. This study aimed to investigate the chemical composition of the leaf essential oil of A. monogyna and evaluate its antioxidant, anti-inflammatory, and antibacterial activities. Materials and Methods: The essential oil was extracted by hydrodistillation and analyzed by GC–MS. Antioxidant activity was assessed by the ABTS•⁺ assay, nitric oxide (NO) inhibition was determined in LPS-stimulated RAW 264.7 macrophages, and antibacterial activity was evaluated using the broth microdilution method. Results: A total of 47 compounds were identified, accounting for 99.21% of the total oil, dominated by sesquiterpene hydrocarbons (50.99%) and oxygenated sesquiterpenes (36.84%). The main constituents were guaiol (13.48%), germacrene D (10.31%), bulnesol (9.85%), and bicyclogermacrene (8.26%). The essential oil exhibited moderate antioxidant activity (IC50 = 61.64 ± 1.13 µg/mL), significant NO inhibitory effect (IC50 = 56.35 ± 2.57 µg/mL), and selective antibacterial activity against Gram-positive bacteria (Staphylococcus aureus, Bacillus subtilis, Lactobacillus fermentum). Conclusion: The essential oil of A. monogyna demonstrates promising antioxidant, anti-inflammatory, and antibacterial potentials, suggesting its value as a natural source of bioactive compounds for pharmaceutical applications.